Corrosion-resistant piston rod material and preparation method thereof

By using carbon-doped porous boron nitride/graphite composite as impurity remover during the smelting process of alloy steel, the problem of uneven composition of alloy steel is solved, which significantly improves the Its corrosion resistance.

CN119121073AInactive Publication Date: 2024-12-13NINGBO AITIAN AUTO PARTS CO LTD

Patent Information

Application Number
CN202411295597.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The impurities and oxidative slag inclusions generated by alloy steel and carbon steel during the melting process lead to uneven material composition, reducing the corrosion resistance of steel.

Method used

Using impurities removal agents, the carbon-doped porous boron nitride/graphite composite materials are synthesized by adding boric acid, urea, citric acid and other materials during the smelting process, and the high adsorption properties are used to remove oxygen, hydrogen and oxidative slag inclusions in the steel. Improve the purity of the steel and form a dense structure through quenching and tempering to enhance the corrosion resistance of the material.

Benefits of technology

It significantly improves the corrosion resistance of alloy steel materials, reduces impurities and oxidized slag inclusions, forms a dense and high-density structure, and enhances the purity and corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of alloy steel materials, and discloses a corrosion-resistant piston rod material and a preparation method thereof. A reasonable formula design and a preparation process are adopted, the corrosion-resistant piston rod material is prepared, the corrosion-resistant piston rod material is composed of, by mass, 1.8%-2.8% of C, 8%-12% of Cr, 2.1%-3.5% of Si, 0.3%-0.8% of Mo, 1.5%-3.5% of Cu, 0.2%-0.6% of Mn, 0.01%-0.03% of B and the balance Fe and inevitable impurity elements, and an impurity removal agent is added in the smelting process for impurity removal; compared with a traditional steel material, the steel material has excellent corrosion resistance due to the fact that molten steel obtained after the ingredients are subjected to melting treatment is treated through the impurity removing agent, oxygen, hydrogen and floating oxidation slag inclusion in the molten steel are adsorbed and removed through the excellent adsorption capacity of the impurity removing agent, the purity of the molten steel is improved, and the service life of the steel material is prolonged. And therefore, impurities of the cast alloy steel material are reduced, and the corrosion resistance of the alloy steel material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy steel materials, and in particular to a corrosion-resistant piston rod material and a preparation method thereof. Background Art

[0002] Piston rods are mainly used in hydraulic and pneumatic, engineering machinery, automobile manufacturing, guide posts of plastic machinery, rollers of packaging machinery and printing machinery, textile machinery, axles for conveying machinery, linear optical axes for linear motion, etc. There are many materials used to make piston rods, such as aluminum alloy, carbon steel, alloy steel, stainless steel and titanium alloy, among which alloy steel and carbon steel are mostly used to prepare piston rods. However, both steel materials have certain impurities during synthesis, and oxidation inclusions will be produced during the melting process. These impurities and oxidation inclusions will cause uneven material composition and discontinuous surface film in steel. Corrosive ions in the surrounding environment will preferentially adsorb on these defective positions, combine with metal cations to produce soluble compounds, destroy the surface passivation film, and further erode the matrix, which causes the corrosion resistance of steel to decrease.

[0003] Therefore, in order to improve the corrosion resistance of steel, it is necessary to treat the impurities and oxide inclusions in the molten steel and remove them in the molten steel to improve the purity of the molten steel and thereby improve the corrosion resistance of the steel. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a corrosion-resistant piston rod material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A corrosion-resistant piston rod material, composed of the following components in mass percentage: C: 1.8%-2.8%, Cr: 8%-12%, Si: 2.1%-3.5%, Mo: 0.3%-0.8%, Cu: 1.5%-3.5%, Mn: 0.2%-0.6%, B: 0.01%-0.03%, the remainder being Fe and unavoidable impurity elements, and an impurity remover is added during the smelting process for impurity removal; The preparation method comprises the following steps: Step S1: adding C, Cr, Si, Mo, Cu, Mn, B and the balance of Fe into a vacuum melting furnace according to the mass percentage for smelting at a smelting temperature of 780-800°C to obtain an initial alloy steel liquid after complete melting, adding an impurity remover for refining for 20-50 minutes, and then slagging and keeping warm for 30 minutes to obtain an alloy steel liquid; Furthermore, the amount of the impurity remover in step S1 is 1.2wt%-2.4wt% of the initial alloy steel liquid; Step S2: Casting the molten steel in step S1 at a casting temperature of 1500-1550° C. to obtain an alloy steel ingot; Step S3: quenching, tempering and cooling the alloy steel ingot in step S3 in sequence to obtain a corrosion-resistant piston rod material; Furthermore, in step S3, the quenching temperature of the alloy steel ingot is 800-1000° C., and the quenching time is 2-4 hours; Furthermore, in step S3, the tempering temperature is 200-400° C., and the tempering time is 3-5 h.

[0006] The impurity remover is prepared by the following steps: Step A1: Add boric acid, urea, citric acid and sodium dodecyl sulfate to an ethanol solution, heat and stir at 80-90° C. for 4-6 hours, filter, wash with water and dry to obtain carbon-doped boron nitride; Step A2: mixing and grinding carbon-doped boron nitride, graphite powder and ammonium sulfate, transferring the ground product into a quartz crucible, and heat treating it in nitrogen at 1350-1450° C. for 3-4 hours to obtain a porous boron nitride / graphite composite material; Step A3: adding the porous boron nitride / graphite composite material to ethanol and mixing and stirring for 30 minutes, adding niobium powder and tantalum powder to ultrasonically disperse under nitrogen, and then distilling under reduced pressure to obtain an impurity remover; Furthermore, in step A1, the usage ratio of boric acid, urea, citric acid, sodium dodecyl sulfate and ethanol solution is 2-6 g: 2.1-6.3 g: 1.1-2.1 g: 0.5-1.35 g: 100 mL, and the volume ratio of ethanol to deionized water in the ethanol solution is 1:1; Further, in step A2, the mass ratio of carbon-doped boron nitride, graphite powder and ammonium sulfate is 1-3:3-5:0.01-0.05; Furthermore, in step A3, the usage ratio of porous boron nitride / graphite, ethanol, niobium powder and tantalum powder is 5-10g: 100g: 1.5-3.5g: 0.3-0.5g.

[0007] Beneficial effects of the present invention: The present invention adopts reasonable formula design and preparation process to prepare a corrosion-resistant piston rod material. Compared with traditional steel materials, the material has excellent corrosion resistance. This is because the molten steel obtained after the ingredients are melted is treated with an impurity remover. The excellent adsorption capacity of the impurity remover is utilized to adsorb and remove oxygen, hydrogen and floating oxide inclusions in the molten steel, thereby improving the purity of the molten steel, thereby reducing impurities in the alloy steel material after casting, and improving the corrosion resistance of the alloy steel material.

[0008] The present invention adds an impurity remover when the ingredients are melt-treated. First, boric acid, urea and citric acid are used as boron source, nitrogen source and carbon source respectively to synthesize carbon-doped porous boron nitride, then the boron nitride, graphite and ammonium sulfate are subjected to composite treatment by grinding and calcining to obtain a composite material, and then the SO2 and NH3 corrosive gases generated by the thermal decomposition of ammonium sulfate are used to corrode the surface and interior of the composite material to form a large number of irregular and high-density pores. The increase in pores improves the adsorption performance of the composite material, and the composite material is used as the base of the impurity remover, and the interaction between the polar chemical bonds contained in the composite material and the hydrogen molecules can be utilized to adsorb the composite material to remove the impurities in the molten steel. Hydrogen effectively reduces the hydrogen content in steel alloy materials, reduces needle-shaped pores, greatly improves the purity and density of the matrix, and thus improves the corrosion resistance of the matrix; the ability of carbon-doped boron nitride to absorb oxygen is improved, because the surface of carbon-doped boron nitride can activate oxygen molecules, making them easier to be adsorbed and activated, reducing the presence of oxygen in the matrix, playing a deoxidation role, reducing pores and inclusions, and is conducive to the formation of dense alloy steel; finally, using the excellent pore structure of the composite material, niobium powder and tantalum powder are loaded in the pores, and niobium and tantalum can combine with oxygen to absorb oxygen in the melt, thereby improving the purity of the molten steel and thus improving the corrosion resistance of the alloy steel. In addition, the excellent adsorption performance of the impurity remover can also absorb the oxidized slag in the molten steel and quickly overflow from the melt, making the molten steel purer and improving the purity of the alloy material. DETAILED DESCRIPTION

[0009] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0010] The impurity remover is prepared by the following steps: Step A1: Add boric acid, urea, citric acid and sodium dodecyl sulfate to an ethanol solution, heat and stir the mixture at 80°C for 4 hours, filter, wash with water and dry to obtain carbon-doped boron nitride. The amount ratio of boric acid, urea, citric acid, sodium dodecyl sulfate and ethanol solution is 2g:2.1g:1.1g:0.5g:100mL, and the volume ratio of ethanol to deionized water in the ethanol solution is 1:1; Step A2: mixing and grinding carbon-doped boron nitride, graphite powder and ammonium sulfate, transferring the ground product into a quartz crucible, and heat treating it at 1350° C. for 3 h in nitrogen to obtain a porous boron nitride / graphite composite material, wherein the mass ratio of carbon-doped boron nitride, graphite powder and ammonium sulfate is 1 g: 3 g: 0.01 g; Step A3: Add the porous boron nitride / graphite composite material into ethanol and mix and stir for 30 minutes. Under nitrogen conditions, add niobium powder and tantalum powder for ultrasonic dispersion, and then distill under reduced pressure to obtain an impurity remover. The amount ratio of porous boron nitride / graphite, ethanol, niobium powder and tantalum powder is 5g:100g:1.5g:0.3g. Example

[0011] The impurity remover is prepared by the following steps: Step A1: Add boric acid, urea, citric acid and sodium dodecyl sulfate to an ethanol solution, heat and stir the mixture at 85°C for 5 hours, filter, wash and dry to obtain carbon-doped boron nitride. The amount ratio of boric acid, urea, citric acid, sodium dodecyl sulfate and ethanol solution is 4 g: 4.2 g: 1.6 g: 0.9 g: 100 mL, and the volume ratio of ethanol to deionized water in the ethanol solution is 1:1. Step A2: mixing and grinding carbon-doped boron nitride, graphite powder and ammonium sulfate, transferring the ground product into a quartz crucible, and heat treating it at 1400° C. for 3.5 h in nitrogen to obtain a porous boron nitride / graphite composite material, wherein the mass ratio of carbon-doped boron nitride, graphite powder and ammonium sulfate is 2 g:4 g:0.03 g; Step A3: Add the porous boron nitride / graphite composite material into ethanol and mix and stir for 30 minutes. Under nitrogen conditions, add niobium powder and tantalum powder for ultrasonic dispersion, and then distill under reduced pressure to obtain an impurity remover. The amount ratio of porous boron nitride / graphite, ethanol, niobium powder and tantalum powder is 7.5g:100g:2.5g:0.4g. Example

[0012] The impurity remover is prepared by the following steps: Step A1: Add boric acid, urea, citric acid and sodium dodecyl sulfate to an ethanol solution, heat and stir the mixture at 90°C for 6 hours, filter, wash with water and dry to obtain carbon-doped boron nitride. The amount ratio of boric acid, urea, citric acid, sodium dodecyl sulfate and ethanol solution is 6 g: 6.3 g: 2.1 g: 1.35 g: 100 mL, and the volume ratio of ethanol to deionized water in the ethanol solution is 1: 1. Step A2: mixing and grinding carbon-doped boron nitride, graphite powder and ammonium sulfate, transferring the ground product into a quartz crucible, and heat treating it at 1450° C. for 4 h in nitrogen to obtain a porous boron nitride / graphite composite material, wherein the mass ratio of carbon-doped boron nitride, graphite powder and ammonium sulfate is 3 g:5 g:0.05 g; Step A3: Add the porous boron nitride / graphite composite material into ethanol and mix and stir for 30 minutes. Under nitrogen conditions, add niobium powder and tantalum powder for ultrasonic dispersion, and then distill under reduced pressure to obtain an impurity remover. The amount ratio of porous boron nitride / graphite, ethanol, niobium powder and tantalum powder is 10g:100g:3.5g:0.5g. Example

[0013] A corrosion-resistant piston rod material, composed of the following components in mass percentage: C: 1.8%, Cr: 8%, Si: 2.1%, Mo: 0.3%, Cu: 1.5%, Mn: 0.2%, B: 0.01%, the balance being Fe and unavoidable impurity elements, and an impurity remover is added during the smelting process to remove impurities; The preparation method comprises the following steps: Step S1: adding C, Cr, Si, Mo, Cu, Mn, B and the balance of Fe into a vacuum melting furnace according to the mass percentage for smelting at a smelting temperature of 780°C to obtain an initial alloy steel liquid after complete melting, adding an impurity remover for refining for 20 minutes, and then slagging and keeping warm for 30 minutes to obtain an alloy steel liquid, wherein the amount of the impurity remover is 1.2wt% of the initial alloy steel liquid; Step S2: Casting the molten steel in step S1 at a casting temperature of 1500° C. to obtain an alloy steel ingot; Step S3: The alloy steel ingot in step S3 is quenched, tempered and cooled in sequence to obtain a corrosion-resistant piston rod material. The quenching temperature of the alloy steel ingot is 800°C, the quenching time is 2h, the tempering temperature is 200°C, and the tempering time is 3h. Example

[0014] A corrosion-resistant piston rod material, composed of the following components in mass percentage: C: 2.4%, Cr: 10%, Si: 2.7%, Mo: 0.5%, Cu: 2.5%, Mn: 0.4%, B: 0.02%, the balance being Fe and unavoidable impurity elements, and an impurity remover is added during the smelting process to remove impurities; The preparation method comprises the following steps: Step S1: adding C, Cr, Si, Mo, Cu, Mn, B and the balance of Fe into a vacuum melting furnace according to the mass percentage for smelting at a smelting temperature of 790°C to obtain an initial alloy steel liquid after complete melting, adding an impurity remover for refining for 30 minutes, and then slagging and keeping warm for 30 minutes to obtain an alloy steel liquid, wherein the amount of the impurity remover is 1.8wt% of the initial alloy steel liquid; Step S2: Casting the molten steel in step S1 at a casting temperature of 1550° C. to obtain an alloy steel ingot; Step S3: The alloy steel ingot in step S3 is quenched, tempered and cooled in sequence to obtain a corrosion-resistant piston rod material. The quenching temperature of the alloy steel ingot is 900°C, the quenching time is 3h, the tempering temperature is 300°C, and the tempering time is 4h. Example

[0015] A corrosion-resistant piston rod material, composed of the following components in mass percentage: C: 2.8%, Cr: 12%, Si: 3.5%, Mo: 0.8%, Cu: 3.5%, Mn: 0.6%, B: 0.03%, the balance being Fe and unavoidable impurity elements, and an impurity remover is added during the smelting process to remove impurities; The preparation method comprises the following steps: Step S1: adding C, Cr, Si, Mo, Cu, Mn, B and the balance of Fe into a vacuum melting furnace according to the mass percentage for smelting at a smelting temperature of 800°C to obtain an initial alloy steel liquid after complete melting, adding an impurity remover for refining for 50 minutes, and then slagging and keeping warm for 30 minutes to obtain an alloy steel liquid, wherein the amount of the impurity remover is 2.4wt% of the initial alloy steel liquid; Step S2: Casting the molten steel in step S1 at a casting temperature of 1550° C. to obtain an alloy steel ingot; Step S3: The alloy steel ingot in step S3 is quenched, tempered and cooled in sequence to obtain a corrosion-resistant piston rod material. The quenching temperature of the alloy steel ingot is 1000°C, the quenching time is 4h, the tempering temperature is 400°C, and the tempering time is 5h.

[0016] Comparative Example 1 A piston rod material, which differs from Example 6 in that the impurity remover prepared in Example 3 is replaced by commercially available refining agent NK-2, and the rest is the same.

[0017] The piston rod materials prepared in Examples 4-6 and Comparative Example 1 were subjected to performance tests: Corrosion resistance test: According to NACE TM 0177-2016 standard, hydrogen sulfide corrosion resistance test was carried out and the surface of the sample was observed; Elongation test: Tested in accordance with GB / T 3077-2015 "Alloy Structural Steel" standard; Tensile strength test: Tested in accordance with GB / T 3077-2015 "Alloy Structural Steel" standard; The test results are shown in the following table: Corrosion resistance Elongation / % tensile strength / % Example 4 No obvious phenomenon 16.6 976 Example 5 No obvious phenomenon 16.8 994 Example 6 No obvious phenomenon 17.1 1013 Comparative Example 1 Slight corrosion 16.2 897 It can be seen from the above table that the piston rod material prepared by the present invention has excellent corrosion resistance, elongation and tensile strength.

[0018] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A corrosion-resistant piston rod material, characterized in that ,, composed of the following components in mass percentage: C: 1.8%-2.8%, Cr: 8%-12%, Si: 2.1%-3.5%, Mo: 0.3%-0.8%, Cu: 1.5%-3.5%, Mn: 0.2%-0.6%, B: 0.01%-0.03%, the balance is Fe and unavoidable impurity elements, and impurity removers are added during the smelting process for impurity removal; The impurity remover is prepared by the following steps: Step A1: Add boric acid, urea, citric acid and sodium dodecyl sulfate to an ethanol solution, heat and stir at 80-90° C. for 4-6 hours, filter, wash with water and dry to obtain carbon-doped boron nitride; Step A2: mixing and grinding carbon-doped boron nitride, graphite powder and ammonium sulfate, transferring the ground product into a quartz crucible, and heat treating it in nitrogen at 1350-1450° C. for 3-4 hours to obtain a porous boron nitride / graphite composite material; Step A3: Add the porous boron nitride / graphite composite material into ethanol and stir for 30 minutes. Add niobium powder and tantalum powder to perform ultrasonic dispersion under nitrogen, and then perform vacuum distillation to obtain an impurity remover.

2. A corrosion-resistant piston rod material according to claim 1, characterized in that: In step A1, the usage ratio of boric acid, urea, citric acid, sodium dodecyl sulfate and ethanol solution is 2-6 g: 2.1-6.3g:1.1-2.1g:0.5-1.35g:100mL, the volume ratio of ethanol and deionized water in the ethanol solution is 1:

1.

3. The corrosion-resistant piston rod material according to claim 1, characterized in that: In step A2, the mass ratio of carbon-doped boron nitride, graphite powder and ammonium sulfate is 1-3:3-5:0.01-0.

05.

4. The corrosion-resistant piston rod material according to claim 1, characterized in that: In step A3, the usage ratio of porous boron nitride / graphite, ethanol, niobium powder and tantalum powder is 5-10g:100g:1.5-3.5g:0.3-0.5g.

5. The method for preparing a corrosion-resistant piston rod material according to claim 1, characterized in that: The following steps are involved: According to the mass percentage, C, Cr, Si, Mo, Cu, Mn, B and the remaining Fe are added into a vacuum melting furnace for smelting at a smelting temperature of 780-800°C. After being completely melted, an initial alloy steel liquid is obtained, and then an impurity remover is added for refining for 20-50 minutes, and then slag is removed and kept warm for 30 minutes to obtain an alloy steel liquid; Step S2: Casting the molten steel in step S1 at a casting temperature of 1500-1550° C. to obtain an alloy steel ingot; Step S3: The alloy steel ingot in step S3 is sequentially quenched, tempered, and cooled to obtain a corrosion-resistant piston rod material.

6. The method for preparing a corrosion-resistant piston rod material according to claim 5, characterized in that: The dosage of the impurity remover in step S1 is 1.2wt%-2.4wt% of the initial alloy steel liquid.

7. The method for preparing a corrosion-resistant piston rod material according to claim 5, characterized in that: In step S3, the quenching temperature of the alloy steel ingot is 800-1000°C, and the quenching time is 2-4h.

8. The method for preparing a corrosion-resistant piston rod material according to claim 5, characterized in that: In step S3, the tempering temperature is 200-400° C., and the tempering time is 3-5 hours.

Citation Information

Patent Citations

  • Wear-resistant alloy steel and preparation method thereof

    CN114032474A

  • Platinum-iridium-palladium-rhodium alloy material and preparation method thereof

    CN117604316A

Cited By

  • Anti-cracking aluminum alloy material for threshold beam of new energy automobile

    CN120210606A